The impact of traffic flow structure on traffic safety: the case of Slovenian motorways - Zanne, Marina; Groznik, Aleš (Transport, 2018)
Road traffic accident is an accident on a public road in which at least one moving vehicle has been involved and material damage or injury or death has occurred. Traffic accidents occur for various reasons, with one of them being the transport infrastructure and next the condition of traffic environment. Motorways are considered to be the safest roads, which have initially been planned as dedicated roads intended to be travelled only by personal cars, but the evolution of modal split of freight transport in Europe is causing the heterogeneity of traffic flows on these roads, which consequently affects the traffic safety. The aim of this paper is to explore the effects of changing volume and structure of traffic flows on road safety on Slovenian motorways. After the exhaustive analysis of past data, the paper provides different models for forecasting traffic safety on Slovenian motorways.First published online 29 March 2016